Factors associated with the incidence of stunting in toddlers aged 12-59 months - Agil Prasetyo; Kasyani Kasyani; Vinna Rahayu Ningsih; Sri Astuti Siregar; Silvia Mawarti Perdana (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Stunting is a nutritional issue that has been a major focus of the Indonesian government. Stunting is caused by chronic malnutrition. Stunting can have both short-term and long-term impacts. Betara Kiri Village has the highest stunting rate. Purpose: This study aims to determine the factors associated with stunting in toddlers aged 12-59 months in Betara Kiri Village, within the Parit Deli Community Health Center (Puskesmas) working area, in 2024. Method: This research is a quantitative study with a case-control design. Data analysis was performed using the chi-square test. The case samples of this study were toddlers aged 12–59 months who experienced stunting and the control samples were toddlers aged 12–59 months who did not experience stunting, with a total sample of 60 consisting of 20 cases and 40 controls from a total population of 134. Data collection was carried out by measuring the height/height of toddlers and interviews using questionnaires. This study took place in Betara Kiri Village, within the working area of ​​the Parit Deli Community Health Center, from July 16, 2024 to September 8, 2025. Results: Most toddlers were exclusively breastfed (75.0%) and had no history of infection (85.0%). More than half of the mothers had low education (51.7%) and were short in stature (51.7%), while the majority attended ANC visits (81.7%), had a low-risk gestational age (75.0%), normal birth spacing (90.0%), low parity (93.3%), and family income above the minimum wage () (63.3%). This study found that exclusive breastfeeding (p=0.027), history of ANC visits (p=0.031), family income (p=0.004), history of infectious diseases (p=0.464), maternal education level (p=0.083), maternal age during pregnancy (p=0.114), birth spacing (p=0.089), parity (p=0.595) and maternal height (p=0.089) were related to the results. Conclusion: It can be concluded that exclusive breastfeeding, history of ANC visits, and family income are associated with stunting. It is hoped that community health centers can improve the quality of exclusive breastfeeding, monitor regular ANC visits, and provide education to low-income families about the importance of balanced nutrition.